THE EFFECT OF WORK INSTRUCTION AND PRODUCTION QUALITY ON PRODUCTION PERFORMANCE AT PT KAWAI INDONESIA (PLANT 3), INDOTEISEI AREA, CIKAMPEK DISTRICT, KARAWANG REGENCY (POLITEKNIK LP3I JAKARTA, 2026)
The objective of this research is to examine the effect of work instruction and production quality on production performance at PT Kawai Indonesia (Plant 3). The research was conducted in the Production Department, focusing on the Assembly Line Production and Quality Control divisions. A quantitative research method was employed and data were collected through questionnaires distributed to a sample of 53 respondents. The data analysis using descriptive statistics, instrument tests, classical assumption tests, multiple linear regression, hypothesis testing (T-test and F-test) and the coefficient of determination. The results show that work instruction, production quality and production performance are generally categorized as high. The T count (1.290) < T table (2.009), significance value (0.203 > 0.05), the work instruction does not have a significant effect on production performance and T count (3.102) > T table (2.009), significance value (0.003 < 0.05), the production quality has a significant effect on production performance. The F count (23.851) > F table (3.18), significance value (0.000 < 0.05), the work instruction and production quality have a simultaneous effect on production performance and the Adjusted R2 of 0.468 indicates that 46.8% of production performance explained by the independent variables, while 53.2% is influenced by other factors.